ANALYSIS OF CO-CREATION EXPERIENCE TOWARDS A CREATIVE CITY AS A TOURISM DESTINATION AND ITS IMPACT ON REVISIT INTENTION - HURRIYATI, Ratih; SOFWAN, Dara Myrna Pusparani (Journal of Environmental Management and Tourism, 2016)
Creation of a creative city requires a major role of all stakeholders. It should be in the context of making the creative city as a tourism destination. Tourists play an active role through collaboration with travel and other tourism related business entrepreneurs. Co-creation experience can become a model that promotes cooperation through creative activities between travel business propriators with tourists. The purpose of this study was to investigate the effect of co-creation experience on a creative city as a tourism destination, as well as its impacts on travelers’ intention to revisit the city of Bandung. This research employed descriptive analysis and verification methods. The size of population was 5,627,421 people and the size of the sample was 390 people. Data source consisted of secondary and primary data. The data collecting techniques consisted of interviews, observations, questionnaires, and literature review. This study utilized Structural Equation Model (SEM) with AMOS program version 21 for IBM. Results of the study revealed that the implementation of co-creation experience is good. Bandung as atourism destination is considered perfect in creativity; and the number of tourists who intend to revisit Bandung is high, meaning that Bandung is a good place to revisit. Co-creation experience gives positive influence on creative city as a tourism destination. A creative city- as a tourism destination contributes positively on the attitude of the tourists. Co-creation experience has a positive influence on revisit intention of an individual.
Keywords: co-creation experience; tourism destinations; revisit intention